2011
DOI: 10.1021/jm201407j
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Hydroxyamidines as Amide Isosteres: Discovery of Oxadiazolines and Oxadiazines as Potent and Highly Efficacious γ-Secretase Modulators in Vivo

Abstract: Cyclic hydroxyamidines were designed and validated as isosteric replacements of the amide functionality. Compounds with these structural motifs were found to be metabolically stable and to possess highly desirable pharmacokinetic profiles. These designs were applied in the identification of γ-secretase modulators leading to highly efficacious agents for reduction of central nervous system Aβ(42) in various animal models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 52 publications
(48 reference statements)
1
30
0
Order By: Relevance
“…94 A conformational constraint was engineered between the amide carbonyl and the α-methyl carbon via a cyclized hydroxy amidine (oxadiazoline) which maintains the potential hydrogen bond acceptor of the amide. Rewardingly, compound 3 had good potency in cells (EC 50 = 58 nM).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…94 A conformational constraint was engineered between the amide carbonyl and the α-methyl carbon via a cyclized hydroxy amidine (oxadiazoline) which maintains the potential hydrogen bond acceptor of the amide. Rewardingly, compound 3 had good potency in cells (EC 50 = 58 nM).…”
mentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 A ring expansion of the oxadiazolines by the Schering group led to the discovery of the oxadiazine scaffold. 94,95 A trifluorophenyl was substituted onto either the C3 or C4 position of the fused oxadiazine to afford potent compounds with unfortunately high cLogPs (4.6) and low MPO scores (3.4). Substitution at the C3 position afforded compound 5 which demonstrated good in vitro potency (EC 50 = 48 nM).…”
mentioning
confidence: 99%
“…Structural modifications have been extensively performed on several classes of compounds. For example, analogs of the arylimidazole containing the olefin linker scaffold have been developed, namely oxadiazine (compounds 79 and 80 ) and oxadiazepine (compound 81 ) . Further studies substituted the olefin linker with a nitrogen linker as shown in aniline‐based compounds containing benzimidazole (compound 82 ), indazole (compound 83 ), benzoxazole (compound 84 ), pyrimidine fused with five‐ or six‐membered rings (compounds 85 ‐ 87 ) and pyrimidomorpholine (compounds 88 ‐ 90 ).…”
Section: γ‐Secretase Inhibitorsmentioning
confidence: 99%
“…Clinical trials involving 33 revealed that it decreases plasma Aβ levels in humans and lends support to the development of more improved compounds. One improvement was the insertion of an oxadiazoline ring that resulted on compound 34 (Figure ) with Aβ 42 EC 50 =29 n m , which is able to decrease the amount of Aβ 42 by 66 %; however, it shows poor CNS druglike properties . Another interesting study resulted in compound 36 (Figure ), which presents high potency (EC 50 =16 n m ), decreased Aβ 42 by 62 %, and has improved druglike properties; however, it shows indications of liver toxicity .…”
Section: γ‐Secretasementioning
confidence: 99%